A few remarks about importance of avifauna of Pu Huong nature reserve in north - central region, Vietnam - Thao, Hoang Ngoc; Cu, Nguyen (Academia Journal of Biology, 2014)
Pu Huong nature reserve located in Nghean province, North part, Vietnam. Field Surveys on Birds in the Pu Huong nature reserve were carried out within April - September, 2004; March - November, 2006 and March - November, 2007 in Chauquang commune (Quyhop district); Dienlam and Chauhoan commune (Quychau district); Quangphong commune (Quephong district) and Ngamy commune (Tuongduong district), Nghean province. A total of 38 species of birds that are importance conservation: There are 12 species of birds were listed in Vietnam Red Data Book 2007 (Endangered: 2 species, Vulnerable: 6 species, Lower risk: 3 species and Data deficient: 1 species); 9 species of birds in Theatened birds of Asia (BirdLife International 2003) and 2006 IUCN Red List of Threatened Species (Vulnerable: 2 species, Near threatened: 7 species); In CITES 2003, there are 28 species, including 2 species in Appendix I and 26 species in Appendix II; And there are 11 species were listed in Decision Number 32/2006/ND-CP of the Government of Vietnam, 4 species in Groups IB and 7 species in Groups IIB (see tables 1). There are 9 species of birds that are international importance conservation, and 2 restricted - range species of North Central Viet Nam that are Crested Argus (Rheinardia ocellata) and Short-tailed Scimitar Babbler (Jabouilleia danjoui). 25 species have been recorded for the Biome-restricted species of Chinese-Himalaya Subtropical forests and 15 species for Indochina Moist forest and 5 species for Indo-Malaya tropical dry forests (see tables 2). Table 3 shows the result by comparison between Pu Huong and other Important Bird Areas in North Central Region of Vietnam. The result of comparison shows that Pu Huong nature reserve have enough conditions for additional to Importance Bird areas of Vietnam.